3-(1-Adamantylamino)-3-methyl-1-phenylquinoline-2,4(1H,3H)-dione - Mahmoodi, Niusha (International Union of Crystallography, 2009)
The structure of the title compound, C(26)H(28)N(2)O(2), contains essentially planar quinoline and benzene rings, the maximum deviations from the best plane being 0.086 (2) and 0.0056 (19) Å, respectively; the dihedral angle between the rings is 82.87 (4)°. The adamantane cage consists of three fused cyclohexane rings in classical chair conformations, with C—C—C angles in the range 107.85 (15)–111.35 (15)°. Enantiomers are linked alternately into chains along the c axis via short N—H⋯O interactions and further C–H⋯π interactions stabilize pairs of enantiomers, forming a two-dimensional network.